2016
DOI: 10.1161/jaha.115.003168
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions Following Endovascular Therapy for Critical Limb Ischemia: Associations With Wound Healing, Major Adverse Limb Events, and Mortality

Abstract: BackgroundThe significance of hospital readmission after endovascular therapy for critical limb ischemia (CLI) is not well established. We sought to investigate the incidence, timing, and causes of readmissions after endovascular therapy for CLI and whether readmission is associated with major adverse limb events (MALE) or mortality.Methods and ResultsThis was a retrospective study of 252 patients treated with endovascular therapy for CLI. During median follow‐up of 381 days (interquartile range [IQR], 115–718… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Further, CLI is the most common cause of readmission in these patients. 6,7,15 The study has several important findings. The overall 30-day readmission rate for a diagnosis of CLI was 5%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, CLI is the most common cause of readmission in these patients. 6,7,15 The study has several important findings. The overall 30-day readmission rate for a diagnosis of CLI was 5%.…”
Section: Discussionmentioning
confidence: 96%
“…This study evaluates the national 30-day CLI-related readmission rates for patients admitted initially with a primary discharge diagnosis of CLI. 7 We have focused on readmissions specifically due to CLI rather than all-cause readmissions as we wished to understand the impact of current management practices on outcomes. Further, CLI is the most common cause of readmission in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Reed et al [42,43] in a retrospective study of 179 patients with CLI and tissue loss, demonstrated through the Kaplan-Meyer statistical analysis, that the probability of major adverse events (MALE-major amputation, surgical endarterectomy, or bypass) was higher in patients with trophic lesions that did not heal within four months of revascularization (log-rank P < 0.0001) compared to those with healed lesions. Patients with non-healing lesions also had a higher rate of amputation (HR, 9.0, 95% CI, 2.6–31.1; P = 0.0004), while patients with lesions healed in three months showed the lowest amputation rate (log-rank, P = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with non-healing lesions also had a higher rate of amputation (HR, 9.0, 95% CI, 2.6–31.1; P = 0.0004), while patients with lesions healed in three months showed the lowest amputation rate (log-rank, P = 0.04). The same authors have also published a retrospective study of 252 patients treated with endovascular CLI procedures and are re-hospitalized after 30 to 180 days for unhealed trophic lesions [43]. From this data it is clear that chronic wounds, both arterial and mixed arterial/venous, represent a strong unmet medical need so far.…”
Section: Discussionmentioning
confidence: 99%